Bizzy Bear ambulance rescue - Davies, Benji (Somerville, Massachusetts Nosy Crow, an imprint of Candlewick Press, 2018)
Push and pull the sliders and tabs to join Bizzy Bear the paramedic as he rides to the rescue in his ambulance
Cover title
Rhymes and Songs
Ages 0-3
Keywords: Ambulances -- Juvenile fiction; Bears -- Juvenile fiction; Stories in rhyme; Toy and movable books -- Specimens; Ambulances -- Fiction; Bears -- Fiction; Board books; Stories in rhyme; Toy and movable books; Board books